2020
DOI: 10.19102/icrm.2020.1100902
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Pediatric Atrioventricular Nodal Re-entrant Tachycardia

Abstract: Catheter ablation is considered as the standard treatment for all patients with symptomatic drug-refractory tachyarrhythmia. The safety and efficacy of the procedure in the adult population is well-established. Due to the small size of the patient and difficulty in attaining venous access, infants are rarely subjected to radiofrequency ablation. Here, we report a case of drug-refractory AV nodal re-entrant tachycardia in a two-year-old child. Radiofrequency ablation was performed with a 5-Fr sized medium-curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Factors such as smaller blood vessels and cardiac chamber volume make RFA more challenging and complex in younger and lower-weight infants. However, recent studies have shown that the incidence of catheter ablation complications in lower-weight patients is not higher [ 10 – 12 ]. Therefore, the decision of whether to choose RFA for these patients remains controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as smaller blood vessels and cardiac chamber volume make RFA more challenging and complex in younger and lower-weight infants. However, recent studies have shown that the incidence of catheter ablation complications in lower-weight patients is not higher [ 10 – 12 ]. Therefore, the decision of whether to choose RFA for these patients remains controversy.…”
Section: Introductionmentioning
confidence: 99%